(untitled) (Bangladesh Journal of Medical Science, 2015)
Objectives: The purpose of this study were (i) to assess the knowledge, attitudes and practice (KAP) and impact of socioeconomic factors upon the prevalence of pre-diabetes and diabetes (ii) compute a diabetes risk score and (iii) estimate the undiagnosed prevalence of hypertension amongst a large adult population in rural Bangladesh. Methods/design: A sample of 3104 adults aged ?30 years were interviewed from a cluster sample of 18 villages in the Banshgram Union of the Narail District, Bangladesh. Each participant was interviewed using a semi-structured questionnaire that assessed participant knowledge, attitudes and practice (KAP) regarding diabetes, its risk factors, complications and management. Data on demographic details, education, socioeconomic status, medical history, dietary and lifestyle behavior was obtained. Fasting capillary glucose, blood pressure, presenting vision and anthropometric parameters were measured. Participants were stratified into those without diabetes, pre-diabetes, and diagnosed diabetes (known and newly diagnosed). The association of KAP components and other risk factors with diabetes status was assessed. Logistic regression analysis allowed for the development of a non-invasive risk-stratification tool to be developed and implemented for the rural Bangladeshi community. Multinomial logistic regression was applied to report the associations of risk factors with the severity of hypertension. Results and discussion: In Banshgram, over 95% people had not undergone any previous diabetes screening. Baseline demographics estimated the prevalence of diabetes in the sample was 3.2% (n=99). 47% of participants had no formal education. Whilst there is literature on the prevalence of diabetes in urban and semi-urban Bangladesh there is a paucity of evidence examining the impact of KAP of diabetes amongst the general community. We believe that the BPDES has developed a methodology to provide new evidence to guide health policy and targeted population-based interventions in these rural areas. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.367-375